Secure range query based on spatial index - Dingxing Xie; Yanchao Lu; Congjin Du; Jie Li; Li Li (2015 1st International Conference on Industrial Networks and Intelligent Systems (INISCom), 2015)
Sensor network has become an increasingly attractive and advantageous subject recently. More and more demands of data storage and data query have been raised in soft-defined sensor network. Bonnet et al. [1] investigated the problem of database in sensor network. In most of such scenes, data is stored in server instead of local. For this reason, data security [2] is very important. While encryption of outsourced data protects against many privacy threats, it could not hide the access patterns of the users. Protecting user information from leakage or attackers while guaranteeing high efficiency of query is becoming an important problem of concern. In this paper, we discuss secure range query based on spatial index. We build the spatial index on the client instead of the server to keep the information away from the potential threat. While keeping a high efficiency of query, we not only encrypt the data, but also hide the access patterns. That will greatly reduce the risk of data leakage. We do simulations and prove our design to be practicable and effective.